(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The problems in this study indicate that the low interest in learning students is caused by physical and psychological factors such as intelligence, attention, and interest in learning students and the limitations of teaching methods used by teachers. The lack of diversity in the way of delivering material makes students lose focus and makes the learning process feel boring. This study aims to examine the application of wordwall learning media in increasing student interest in learning Islamic Religious Education subjects at SMPN 29 Padang. The method used is qualitative research with a descriptive approach. Research data were obtained through interview techniques, observation, and documentation. The results of this study indicate that the application of wordwall media in Islamic Religious Education learning has a positive impact on student interest in learning, the application is through three ways, namely planning, implementation and reflection. The use of wordwall can increase student interest in learning which is reflected in increased student involvement, student attention, student feelings of pleasure and student interest in learning. The main supporting factors are the interactive appearance of wordwall and game variations while the inhibiting factors include dependence on internet connection and limited question displays. This study concludes that wordwall media is effective in increasing interest in learning Islamic Religious Education at SMPN 29 Padang.